Analyzing the Switch Segments and Types of Switch in Indonesian-English Code Switching and Code Mixing Phenomenon of Elite People in Makassar - Baharuddin Baharuddin (Institut Agama Islam Negeri Palopo, 2020)
This research aimed at finding out speech variety used by elite people in Makassar which was the phenomenon of Indonesia–English code switching and code mixing in four aspects namely (1) conversation function and reasons of code switching by the elite people, (2) the switched segments which were frequently used, (3) combination patterns of code switching, and (4) the types of code switching. In this research both qualitative and quantitative methods were applied. The data were obtained through recording for two hours. The population was the elite people in Makassar who were divided into five groups namely doctors, government officials, lawyers, lecturers, and politicians living in Makassar. There were 100 conversation produced by 25 respondents. The result show that the function of code switching which most frequently occurs in conversation tends to play with English popular expressions. In terms of switched segments, the most frequently used are noun phrases, while the most often employed combination is the combination of verbs (VP) and nouns (NP). In relation to type of code switching, intra-clausal is the most frequently used by the elite people in conversation.